Honey and Healing in the Qur’an: A Multidisciplinary Analysis of Surah Al-Nahl (68–69): العسل والشفاء في القرآن الكريم: تحليل متعدد المناهج لآيتي سورة النحل (68–69) - Fatima Alsaeh; Safa Alrumayh; Najah Baroud; Eman Alsaeh; Amaal Kasheem (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2025)
This study aims to analyze ayat (68–69) of Surah Al-Nahl through a multidisciplinary approach that combines philological and rhetorical analysis of the Qur’anic text with comparisons to modern findings in chemistry, biology, and medical sciences. The methodology emphasizes the centrality of the Qur’anic text and its interpretation by major exegetes such as Al-Tabari and Ibn Kathir, while incorporating experimental results from peer-reviewed scientific research. The study addresses precise linguistic and rhetorical elements, such as the connotation of the verb “awḥā” in the context of the innate inspiration of bees, the meaning of “buṭūnihā” in light of insect anatomy, the lexical and rhetorical variety in “mukhtalifun alwānuhu”, and the sensory and metaphorical implications of “shifāʾun lil-nās.” The findings reveal a striking convergence between Qur’anic depictions and modern scientific studies that demonstrate honey’s antibacterial and anti-inflammatory properties, as well as its variation according to botanical and geographical sources. The study concludes that the Qur’anic text presents an integrated model that unites miraculous eloquence with scientific precision, and calls for a research methodology that combines revelation with empirical knowledge within a reflective and epistemological framework.